(untitled) - Hirsch, James S. (Boston, 2002)
A best-selling author investigates the causes of the twentieth century's deadliest race riot and how its legacy has scarred and shaped a community over the past eight decades. On a warm night in May 1921, thousands of whites, many deputized by the local police, swarmed through the Greenwood section of Tulsa, Oklahoma, killing scores of blacks, looting, and ultimately burning the neighborhood to the ground. In the aftermath, as many as 300 were dead, and 6,000 Greenwood residents were herded into detention camps.
Keywords: African Americans,Racism,African American neighborhoods; History,History,History; 20th century,20th century,20th century; Oklahoma,Tulsa,Oklahoma,Tulsa,Oklahoma,Tulsa